A broadband multilayered nonpolarization resonant reflector - L. Huang; D. Liang; J. Zeng; Y. Xiao; H. Wu (IEEE Photonics Journal, 2015)
A nonpolarization reflector constructed by a multilayered 1-D grating structure with a multisubpart profile is proposed and fabricated. Rigorous coupled-wave analysis for multilayered grating structure is adopted to theoretically investigate the properties of the structure. In addition, experimental verification of theoretical investigation is accomplished. It is shown that in both TE and TM polarized waves, the reflector experimentally demonstrates a wideband reflection spectrum from 1.65 to 1.72 μm, very high reflectivity (R > 97%), and good angular insensitivity of about 24.6°. Moreover, a reasonably good tolerance of fabrication error is also presented by numerical analysis of device performance degeneration resulting from parameter deviations.